Improved analysis of a multirobot graph exploration strategy - Brass, Peter; Vigan, Ivo; Ning Xu (2014 13th International Conference on Control Automation Robotics & Vision (ICARCV), 2014)
In this paper, we present an algorithm for exploring an unknown graph with opaque edges by multiple robots. We show that this algorithm is near optimal on graphs with n vertices and superlinear number of edges (i.e., ω(n) edges), and give an adversarial construction to show that the algorithm does not perform well on cyclic graphs with O(n) edges.